Penyuluhan Kesehatan Reproduksi pada Remaja - Waldatul Hamidah; Febrina Febrina; Riska Pitriyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Ridan Permai Village, within the Bangkinang City Community Health Center (Puskesmas) jurisdiction in Kampar Regency, faces a serious problem related to adolescents' lack of access to health information and services, particularly regarding reproductive health. Survey results revealed that adolescents rarely receive regular health education or checkups, even though they are a vulnerable group to various health problems and behavioral disorders due to their identity-searching phase. The lack of reproductive health education in schools and the community also exacerbates this situation, leading adolescents to tend to obtain information from invalid or incorrect sources. Through the Community Service (PKM) program, a team of lecturers and students conducted a series of activities at SMPN 1 Padang to increase adolescents' knowledge and awareness of reproductive health. Three main approaches were used: direct education, outreach through interactive discussions, and distribution of leaflets as a continuous information medium. In addition, a question-and-answer session provided a space for students to openly share their questions and experiences without embarrassment. This approach was designed to create a participatory, educational atmosphere. These activities aimed not only to increase adolescents' knowledge but also to empower them to prevent the risk of health problems and behavioral disorders. The expected outcome of this activity is increased understanding of reproductive health among adolescents, as well as the formation of collective awareness for maintaining health and positive behaviors among adolescents. Sustainability of the program is also being pursued by involving teachers and school officials as partners in health education. This activity is also expected to serve as an educational model that can be replicated in other schools in Kampar Regency.